Attitudes of patients with severe mental illness towards COVID-19 vaccinations: A preliminary report from a public psychiatric hospital. (November 2021) - Danenberg, Renana; Shemesh, Sharon; Tzur Bitan, Dana; Maoz, Hagai; Saker, Talia; Dror, Chen; Hertzberg, Libi; Bloch, Yuval
Abstract: Background: As patients with severe mental illness are at increased risk for COVID-19 mortality, the issue of willingness to be vaccinated is of extreme importance. Methods: During February 2021 Shalvata Mental Health hospital provided Covid-19 vaccines to its patients. Fifty one patients suffering from severe mental illness, out of 196 patients hospitalized in closed, open or day wards during that period, signed the informed consent and were assessed for their clinical condition (OQ-45), fear of Covid-19 (FCV-19S) and approach to the vaccine (C19-VHS). All patients who were not vaccinated in February 2021 (baseline) were re-approached a month later to assess whether they had gotten vaccinated since. Results: Patients who were not vaccinated at baseline had an oppositional approach to the vaccine, and did not significantly differ in their fear of Covid-19 levels or in levels of clinical severity (t(49) = 2.51, p = 0.02) from those who were vaccinated. From the 29 patients who were not vaccinated at baseline approach to the vaccine was a good predictor to getting vaccinated after one month (79% positive predictive value). Conclusions: The majority of patients suffering from a severe mental illness are willing to get vaccinated, and their decision of whether or not to get vaccinated is based on their viewpoint on the vaccine rather than being an outcome of their level of distress (OQ-45). It is important to allow vaccine accessibility to hospitalized patients, to consider their opinions and to provide useful information to lower vaccine hesitancy and improve vaccination rates.